Secondary amenorrhea in severe Asherman's syndrome: Step by step fertility retrieval by Bettocchi's hysteroscope: Some considerations. Issue 2 (March 2014) - Gizzo, Salvatore; Saccardi, Carlo; Di Gangi, Stefania; Bertocco, Anna; Vendemiati, Lucia; Righetto, Lara; Patrelli, Tito Silvio; D'antona, Donato; Nardelli, Giovanni Battista
Abstract The aim of this report was to define the best diagnostic and therapeutic approach when secondary amenorrhea is related to undiagnosed Asherman syndrome. We present a single case of secondary amenorrhea with a previous diagnosis of alterated hypothalamic-hypophysary regulation, with a component of ovarian function in probable reduction, which was evaluated in our department and resulted affected by Asherman's syndrome IV stage. We describe step by step the diagnosis and treatment of a previously misdiagnosed case of severe Asherman's syndrome. An appropriate diagnosis and adequate treatment are mandatory to allow menses and fertility to be restored when severe Asherman's syndrome occurs.